Evaluating the impact of multicancer early detection testing on health and economic outcomes: Toward a decision modeling strategy. (8th February 2022) - Lipscomb, Joseph; Horton, Susan; Kuo, Albert; Tomasetti, Cristian
Abstract : Emerging data provide initial support for the concept that a single, minimally invasive liquid biopsy test, performed in conjunction with confirmatory radiologic or other diagnostic testing, when indicated, could be deployed on a broad scale to screen individuals for multiple types of cancer. Ideally, such a test could do this in a way that yields a clinically important percentage of true‐positive indications of cancer while minimizing false‐positive signals. Modern decision modeling approaches can and should be deployed to investigate the health and economic consequences of such multicancer early detection (MCED) testing within defined at‐risk populations. In this paper, through small‐scale analyses involving 3 hypothetical MCED‐detectible cancers, the authors illustrate the potential for MCED testing to be cost‐effective, along with the pivotal role of test‐induced stage shift on results. The time is ripe for additional, prospective investigations of the clinical value of MCED testing, the benefits versus the risks for screened populations, and the overall projected impact on health outcomes and costs over time. Abstract : Modern decision modeling approaches can and should be deployed to investigate the health and economic consequences of multicancer early detection (MCED) testing within defined at‐risk populations. Through small‐scale analyses involving 3 hypothetical MCED‐detectible cancers, this report illustrates the potential for MCED testing to be cost effective, along with the pivotal role of test‐induced stage shift on results.